Lignin macromolecule's implication in slowing the biodegradability of urea-crosslinked starch films applied as slow-release fertilizer - Majeed, Z. (Wiley-VCH Verlag, 2017)
High biodegradability of starch is a major limitation for its commercial usage in developing urea-crosslinked starch (UcS) film as slow-release fertilizer. For solving this problem, UcS films were reinforced with 5–20 kraft lignin. Implication of lignin as a macromolecule was tested for slowing the biodegradability of UcS films. These films were biodegraded and characterized in an aerobic soil burial test up to the 60th day. The results were drawn for biodegraded lignin-reinforced films through comparison made with biodegraded control film, which received 0 lignin. The Fourier transform infrared spectroscopy peaks at 1625 and 1665 cm−1 corresponded to UcS and were found to be more conspicuous in biodegraded lignin-reinforced films. Thermogravimetric analysis of biodegraded lignin-reinforced films showed higher thermal stability. This was inferred from the decrease of ∼85.45°C in the thermal decomposition temperature at 5 weight loss (onset temperature), the increase of ∼31.69°C in the thermal decomposition temperature at maximum weight loss, and the increase of ∼12.90 in char. The molecular weight distribution of the biodegraded lignin-reinforced films reduced not more than ∼1 and the polydispersity index was conserved to 1.4. Light microscopy of the biodegraded lignin—reinforced films reduced not more than ∼1 and polydispersity index was conserved to 1.4. Light microscopy of biodegraded lignin-reinforced films showed the shape of starch particles was oblong, less disrupted, and wrinkled. Field-emission electron microscopy showed lignin addition favored more the fungal growth beside formation of cavities. Atomic force microscopy showed the average surface roughness increased 2.00–7.32 times more as a result of residual lignin's accumulation in biodegraded lignin-reinforced films. Based on the understanding of biodegradability in UcS films, a theoretical framework has also been proposed for biodegradability-driven urea-nitrogen release in soil. © 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim